Study on the influence of compaction energy and moisture content on the permeability and compression characteristics of granite-weathered soil - Haibo Lyu; Dongcheng Wei; Jianxiao Gu; Liyun Fan (PLoS ONE, 2026)
The feasibility of reusing granular weathered (GW) soil as foundation fill is closely related to the strength and stability. Initial moisture content and compaction energy were identified as the main factors affecting the strength and deformation behavior of GW soil. GW soil samples were prepared with different initial moisture contents ranging from 7 ~ 15% and compacted under varying compaction energies ranging from 50 ~ 125%, respectively. The results indicate that the permeability coefficient decreases sharply with increasing compaction energy and then gradually stabilizes at higher compaction energy levels, suggesting that compaction energy is the dominant factor governing soil permeability. Higher initial moisture content leads to larger strains due to the presence of thicker adsorbed water films, whereas higher compaction energy enhances interparticle bonding, reduces the void ratio, and increases soil stiffness. In particular, the void ratio is affected by both initial moisture content and compaction energy, highlighting the necessity of incorporating compaction energy into predictive permeability models. Furthermore, a compaction-energy-based permeability prediction model was developed, with the predicted results showing strong agreement with the experimental data. These findings provide practical guidance for optimizing the compaction of GW soil to enhance foundation stability and reduce the risks associated with rainfall infiltration, and seepage failure.